The Influence of Work Motivation and Interpersonal Communication on Social Competence of Public Elementary School Teachers in Cluster IV, Bukit Kapur District, Dumai City - Sriwahyuningsih, Sriwahyuningsih; Natuna, Daeng Ayub; Sumarno, Sumarno (Journal of Educational Sciences, 2022)
This study aims to determine the effect of work motivation and interpersonal communication on the social competence of teachers. The population of this study were teachers of public elementary schools in Cluster IV, Bukit Kapur District, Dumai City. Sampling was done by simple random sampling technique, the sample was set at 91 people. The data was collected by using a questionnaire technique and then analyzed using several linear regression equations and the proof of the hypothesis using the t test, F test, and the coefficient of determination (R2). The results of the t-test of the work motivation variable have a significant effect on the teacher's social competence. Interpersonal communication variables have a significant effect on the social competence of teachers. The results of statistical tests (Test F), simultaneously work motivation and interpersonal communication have a significant effect on the social competence of teachers at SDN Gugus IV Bukit Kapur, Dumai City. Based on the t and F tests, the hypothesis is accepted.